Investigating the Biological Impact of Melatonin on Male Albino Mice: A Comprehensive Characterization - Hanan H. ALQaragholy (Journal of Global Innovations in Agricultural Sciences)
Melatonin (Mel) is a chemical that has been found in bacterial, higher plants, invertebrates, and vertebrates. The plant extract was analyzed using high-performance liquid chromatography (HPLC) to find Mel. Mel concentrations differed greatly, according to the data. The aim of this study was to see how Mel generated from Ziziphus spina-christi leaves affected thyroid, liver enzymes, and lipid profiles in male albino mice. Twenty male mice were divided into four groups, each containing five mice, and were administered intraperitoneally (i.p) injections of Mel in three doses (4, 7 and 10 mg/ml), except for the control group, which received only a dose of normal saline solution. In comparison to the control therapy, the results showed that the Mel dose of 10 mg/ml had the greatest impact on lowering the levels of thyroid hormones (T3 and T4), lowering the levels of the liver enzymes Alanine transaminase (ALT), Aspartate aminotransferase (AST), and Total serum bilirubin (TSB) and lowering lipid profile (cholesterol (CHO), low-density lipoprotein (LDL), very low-density lipoprotein (VLDL), and triglycerides (TG)). In addition to raising the level of high-density lipoprotein (HDL) in mice's blood serum with substantial variations from the control therapy. The review summarizes, this evidence implicates Mel in a broad range of effects with a significant regulatory influence over many of the body's physiological functions. Keywords: Blood serum, Medicinal plants, tryptophan, Rhamnaceae family, methanol, TLC and pineal gland.